Karakteristik Uji Stabilitas Pigmen dan Antioksida Hasil Ekstraksi Pewarna Alami dari Kulit Buah Naga Merah - Thorieq Moh. Yusuf; Ana Nurjanah; Andi Wapa (Lembaga Pengembangan Kinerja Dosen, 2023)
This article aims to determine the level of anthocyanins in natural colors derived from dragon fruit, especially on the skin. Completely Randomized Design (CRD) with SPSS was used as the research method for this article, as well as two treatments, namely variations in solvent volume A and immersion time (B). Each treatment consisted of three levels and three repetitions, namely the first factor of variation in solvent volume (A) consisted of (A1) 0.29%, (A2) 0.432%, (A3) 0.576%. The second factor is the immersion time (B1) 42 hours, (B2) 48 hours, (B3) 72 hours. Extraction of anthocyanin pigment from red dragon fruit skin was carried out using maceration extraction. The test parameters in this study were the color stability test, anthocyanin content test and the yield of dragon fruit peel extract. The pH value was measured using a pocket pH meter. In this study, a spectrophotometer was used to determine the brightness level of anthocyanins. Measurement of the weight % yield of anthocyanin pigment was carried out using the yield formula below. The research results show; (1) the best treatment resulted in extraction using citric acid solvent: water which produced an absorbance of 0.479 – 0.439 at λmax 517 nm; (2) radar antioxidant activity in anthocyanins from dragon fruit peels of 76.71%; (3) the stability of anthocyanin dyes is stable at acidic pH from pH 2 – pH 5, at a temperature of 80˚C and the effect of long exposure to the lamp makes the anthocyanin dyes unstable; and (4) dragon fruit syrup was stable at almost the same pH of dragon fruit syrup without coloring and added dragon fruit syrup, namely 3.42 and 3.89.